Professor Volodymyr Oleksiiovych Shlyakhovenko (on the 80th birth anniversary) (PH Akademperiodyka, 2018)
Volodymyr Shlyakhovenko has been working at the R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the National Academy of Sciences of Ukraine since 1965 after his postgraduate fellowship. In 1967, he got his PhD degree. In 1985, Dr. Shlyakhovenko defended his doctorate thesis “Molecular heterogeneity and complex-forming properties of ribonucleases in leukemia” and got his doctorate degree. Since 1971, Dr. Shlyakhovenko was senior research fellow. In 1979–1984, Dr. Shlyakhovenko was a Deputy Director of the Institute. Prof. V. Shlyakhovenko is an eminent specialist in biochemistry of cancer. His scientific interests center around the study of the enzymes, especially their molecular heterogeneity in cancer cells, and their role in cell proliferation and impairment of cell differentiation. Prof. V. Shlyakhovenko has elaborated the techniques for measuring the nuclease activity and identifying the enzymes in electrophoregrams. His studies on the nuclear proteins are well known among the specialists in the field. Being not only the investigative scientist and talented experimentator but also a gifted inventor, Prof. V. Shlyakhovenko developed the unique sophisticated equipment for electrophoresis in polyacrylamide and agarose gels. His apparatus for electrophoresis in the setting of microgravitation conditions operated successfully on board of the spacecraft of Cosmos series. Prof. V. Shlyakhovenko authored more than 350 scientific papers and 20 inventions. He has supervised seven PhD theses. For many years, he headed a scientific department of our Institute being in charge of several important scientific project devoted to the study of the modifiers of polyamine metabolism and their anticancer effects. He studied the mechanisms of anticancer activity of several substances. In particular, coordination metal-amine complexes were tested thoroughly and their efficacy as the substances targeting the activity of the enzymes involved in polyamine metabolism in cancer has been proved. The team headed by Prof. V. Shlyakhovenko developed and tested the original method for producing polyvalent anticancer vaccines based on polypeptide fraction from cancer cells. The technology for producing DNA oligonucleotides containing CpG fragments of non-methylated DNA has been elaborated and its efficiency as adjuvant in combination with anticancer vaccine has been confirmed. Prof. V. Shlyakhovenko combines his research activity with tremendous organizational work. For many years, he is a member of the Scientific Board and the Specialized Dissertation Advisory Council, the expert of the State Pharmacological Center of the Ministry of Health of Ukraine. For 40 years, Prof. V. Shlyakhovenko was a permanent secretary of the medical section of the Committee on State Awards in Science and Technology. In 2007, Prof. V. Shlyakhovenko was awarded the State Prize of Ukraine in Science and Technology for studying ceruloplasmin and its application in clinical practice. The studies by Prof. V. Shlyakhovenko are always on the front edge of the science. And nowadays he focuses on the search for the markers of tumor growth and monitoring of cancer treatment. The administration and the staff of the Institute, all the colleagues have a great pleasure to congratulate Prof. V. Shlyakhovenko on the occasion of his 80th birthday and to wish him good health, long years of fruitful scientific activity and new scientific achievements. Scientists of R.E. Kavetsky Instituteof Experimental Pathology,Oncology and Radiobiology of the National Academy of Sciences of Ukraine,Editorial Board of “Experimental Oncology”